The Effect of E-Service Quality and Website Quality on E-Loyalty with E-Satisfication as an Mediating Variable at the Bluder Cokro Company - Eka Wawan Febriyanti; Irmawati Irmawati (Proceedings Series on Social Sciences & Humanities, 2024)
The rise of the Indonesian economy after passing through the Covid-19 pandemic, Madiun city specialty food entrepreneurs have a competitive strategy to achieve customer satisfaction so that customer loyalty is maintained in the long term by improving business quality regularly and periodically.This study aims to analyze the effectiveness of e-service quality and website quality on e-loyalty with e-satisfication as a mediating variable at the Cokro bluder company. The number of respondents in this study were 150 respondents who had experience shopping for bluder Cokro products online. The survey of respondents was conducted online using the google form facility so that the technique used to take samples in this study was purposive sampling technique because it was in accordance with certain considerations based on the objectives of this study. The data that has been obtained from respondents then goes through several test stages using the Smart PLS 3.0 program. Outer model there are several tests carried out such as validity test, reliability test and multicollinearity test while the inner model conducts Godness of Fit (Gof) test and hypothesis testing. The results of the analysis explain that e-service quality has a significant positive effect on e-loyalty, e-service quality has a significant positive effect on e-satisfication, website quality has a significant positive effect on e-loyalty, website quality has a significant positive effect on e-satisfication, e-satisfication also has a significant positive effect on e-loyalty so that e-satisfication successfully mediates the relationship between e-service quality and website quality on e-loyalty.